ANALISIS FAKTOR PENYEBAB REWORK PADA PEKERJAAN KONTRUKSI JALAN KOTA PADANG - Dewi Puspa; Yossyafra Yossyafra; Yosritzal Yosritzal (Rang Teknik Journal, 2022)
Rework is a repeat job that is caused by an error from a construction project. In a construction activity almost always happens rework only the quantity is different. The purpose of this study is identify the factors that cause rework, identify the conditions of rework, identify the intensity of rework on road construction work item in the city of Padang. This study uses qualitative methods with a descriptive approach. The result of the study are the main factors that led to road construction rework in Padang city were design and documentation, managerial factor and resources. Little rework conditions occur in road construction work in the city of Padang. The intensity of work items the occur on average rework is rare. Keywords: Rework, Construction project, identification.